Evaluation of barriers to referral for cancer predisposition syndromes in pediatric oncology patients in the United States. Issue 4 (11th February 2022) - Venier, Rosemarie E.; Grubs, Robin E.; Kessler, Elena; Cooper, Kristine L.; Bailey, Kelly M.; Meade, Julia
Abstract: Cancer predisposition syndromes (CPS) are underdiagnosed in the pediatric population, though the diagnosis of a CPS has important implications for the child and their family. CPS are often diagnosed by geneticists or oncologists with expertise in CPS following a malignancy. This requires a member of the care team, most commonly, the treating oncologist to suspect a CPS and refer the patient for CPS assessment. An online survey was distributed to members of the Children's Oncology Group to elucidate current referral practices and barriers to referral for patients suspected to have a CPS. Of the 183 respondents, 86.1% was pediatric oncologists and most (68.5%) used formal guidelines to aid in assessment. Most respondents indicated they would rarely refer patients with tumors highly associated with CPS for genetic assessment. Participants were more likely to refer patients with malignancy and additional features of a CPS than for a specific type of cancer, despite the use of guidelines. Parent knowledge of family history was considered the most challenging barrier to obtaining a family history, though a thorough pedigree was not consistently elicited. Providers indicated the most significant barrier to referral for CPS assessment was priority given the patient's immediate care needs. Identification of these barriers provides direction to focus efforts to increase referrals. Provider education about CPS, clear referral guidelines, and implementation of or increased collaboration with a genetic counselor in the pediatric oncology clinic may encourage CPS assessment and enable oncologists to focus on the patient's immediate care needs.